2020
DOI: 10.3390/met10070872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tool Geometry and Welding Parameters on Friction Stir Welded Lap Joint Formation with AA2099-T83 and AA2060-T8E30 Aluminium Alloys

Abstract: In this paper the effect of tool geometry and welding parameters on friction stir welded lap joints with AA2099-T83 and AA2060-T8E30 aluminium alloys has been investigated through the study of the material flow and weld formation along with the reaction forces during friction stir welding (FSW) for various sets of welding parameters and two FSW tools with different geometrical features. The results showed that welding parameters and tool probe geometry strongly affect the characteristics of the typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…While AA6082 experiences strong softening under high temperature and strain rate conditions, AA5083 presents steady flow behaviour at high tem- The average torque in dissimilar welding also increases with the traverse speed (Figure 4a). Similar findings were also reported by Banik et al [29] and Aldanondo et al [30], although Arora et al [9] stated that torque is little influenced by welding speed. In most of the cases, the evolution of the temperature with the traverse speed supports the variation in torque, that is, the peak temperature decreases with the increase of welding speed (Figure 4b), and the base material presents higher material flow stresses [8], thus requiring greater torque.…”
Section: Welding Torque and Temperaturesupporting
confidence: 85%
“…While AA6082 experiences strong softening under high temperature and strain rate conditions, AA5083 presents steady flow behaviour at high tem- The average torque in dissimilar welding also increases with the traverse speed (Figure 4a). Similar findings were also reported by Banik et al [29] and Aldanondo et al [30], although Arora et al [9] stated that torque is little influenced by welding speed. In most of the cases, the evolution of the temperature with the traverse speed supports the variation in torque, that is, the peak temperature decreases with the increase of welding speed (Figure 4b), and the base material presents higher material flow stresses [8], thus requiring greater torque.…”
Section: Welding Torque and Temperaturesupporting
confidence: 85%
“…Process parameters affect the normal force and temperature in FSW processes. In addition to tools, research has been conducted on process parameters to reduce defects and increase the mechanical strength of FSW joints [ 29 , 30 , 31 , 32 , 33 , 34 ]. Baskoro et al [ 29 ] conducted experiments and analyses for plunge speeds of 2, 3, and 4 mm/min and dwell times of 0, 2, and 4 s in the high-speed micro-friction stir spot welding (µFSSW) of Al A1100 with a thickness of 0.4 mm and revealed that a dwell time of 2 s was the most important welding parameter in the µFSSW process.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [ 33 ] performed FSLW of a 3 mm thick Al (1060Al) sheet and a 1 mm thick stainless steel (SUS321, austenite) sheet using a 6 mm diameter pin, with an insertion depth of 2.8 and 3.2 mm, and found that the greater the tool penetration depth, the greater the tensile strength. Regensburg et al [ 34 ] investigated hooking and IMC formation with the pin lengths at the junctions being 1.8, 2.0, 2.2, 2.4, and 2.6 mm at the lap joint of EN AW1050/CW024A material with a thickness of 2 mm. It was found that plunging into the lower copper sheet of about 0.2 mm by a pin length of 2.2 mm yielded the highest breaking load.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations